2001
DOI: 10.1017/s1357729800058379
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of milk traits in Latxa dairy sheep

Abstract: A total of 7444 lactation records which include milk, fat and protein yields (MY, FY, PY) and fat and protein content (F%, P%) from 6429 Black-Faced Latxa ewes were employed to estimate genetic parameters for milk traits. Traits were standardized to 120 days of lactation. For the calculation of composition traits, not all test-days had their composition measured and therefore a correction taking this into account was included in the analysis. A first-derivative restricted maximum likelihood algorithm was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…Serrano et al (2003) recently reported a heritability estimate of 0.18 for standardised milk yield (120 days) in Manchega ewes. However, heritability estimated for total milk yield in native Spanish dairy sheep breeds such as those of 0.23 and 0.24 for the Churra breed (ElSaied et al, 1998a;Othmane, 2000) and 0.20 and 0.21 for the Latxa breed (Ugarte et al, 1996;Legarra and Ugarte, 2001) are usually higher than those reported here Table 4 Genetic, permanent environmental, residual and phenotypic covariances and genetic (r g ), permanent environmental (r c ) and phenotypic (r p ) correlations among lactation length (LL) in days, 180 days adjusted milk production (MY 180 Barillet, 1997) or Sarda (0.30; Sanna et al, 1997). However, Portolano et al (2001), in Barbaresca siciliana sheep, reported heritability estimates for milk yield standardised to different lactation lengths that always ranged from 0.14 to 0.15 and Nikolau et al (2004) reported different estimates for total milk yield in Lesbos dairy sheep ranging from 0.16 to 0.20.…”
Section: Resultsmentioning
confidence: 99%
“…Serrano et al (2003) recently reported a heritability estimate of 0.18 for standardised milk yield (120 days) in Manchega ewes. However, heritability estimated for total milk yield in native Spanish dairy sheep breeds such as those of 0.23 and 0.24 for the Churra breed (ElSaied et al, 1998a;Othmane, 2000) and 0.20 and 0.21 for the Latxa breed (Ugarte et al, 1996;Legarra and Ugarte, 2001) are usually higher than those reported here Table 4 Genetic, permanent environmental, residual and phenotypic covariances and genetic (r g ), permanent environmental (r c ) and phenotypic (r p ) correlations among lactation length (LL) in days, 180 days adjusted milk production (MY 180 Barillet, 1997) or Sarda (0.30; Sanna et al, 1997). However, Portolano et al (2001), in Barbaresca siciliana sheep, reported heritability estimates for milk yield standardised to different lactation lengths that always ranged from 0.14 to 0.15 and Nikolau et al (2004) reported different estimates for total milk yield in Lesbos dairy sheep ranging from 0.16 to 0.20.…”
Section: Resultsmentioning
confidence: 99%
“…Generally larger estimates of heritability have been previously reported for MS at mature ages for the same four breeds . Legarra and Ugarte (2001) reported an estimate of heritability of 0.20 for Latxa dairy sheep using 120-d repeated lactation records. Baro et al (1994) andEl Saied et al (1999) estimated heritability to be 0.34 and 0.18 for multiple-lactation, test-day milk yield of Spanish Churra milking sheep, respectively.…”
Section: Milk Scorementioning
confidence: 99%
“…Average milk production could be considered low or medium, with yields varying from 70 to 150 kg of milk/lactation (Padeanu 2001). Although, some strains, due to selection and proper nutrition, may be able to produce yields higher than 200 kg of milk/lactation, taking into account the heritability for milk yield that ranges between 0.20 and 0.29 (El-Saied et al 1998;Legarra & Ugarte 2001). The most prominent breeds of this group are Comisana, Karagouniko, Lesvos, Podhale Zackel, Pramenka, Sarda, Sfakion, Turcana, Valachian and Vlahico.…”
Section: Introductionmentioning
confidence: 99%